Pathology of Solid Organ Transplantation - Liapis, Helen.; Liapis, Helen.; Wang, Hanlin L.; Wang, Hanlin L. (Springer Berlin Heidelberg : Imprint: Springer, 2011)
Because of progress in diagnostic transplantation pathology interpretation of transplant biopsies is increasingly becoming an attractive field for general surgical pathologists. The book focuses on the pathology of transplantation in the following organs: kidney, liver, lungs, heart, pancreas and small intestine. An introductory section addresses common entities that may complicate all transplant recipients such as infections, post-transplant lymphoproliferative disease and graft versus host disease, followed by 6 sections with detailed manifestations of rejection in each organ. This comprehensive, well-illustrated book serves the needs and meets the requirements of pathologists in training and those practicing in centers with limited volume of transplant biopsies in daily practice.